Angka Kejadian Diabetes Melitus Tidak Terdiagnosis pada Masyarakat Kota Pekanbaru - Puji Artanti; Huriatul Masdar; Dani Rosdiana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTDiabetes mellitus is a chronic disease and the number is rising in theworldwide. One of risk factors of diabetes mellitus is obesity which can causeinsulin resistance. The purpose of this research was to inform the prevalence ofundiagnosed diabetes mellitus (UDDM) in Pekanbaru community. A crossectionalstudy design was performed November 2013-Desember 2014. Two hundred andthirty six subjects were involved in this research. Based on this research, 100subjects with central obesity detected as undiagnosed diabetes mellitus.Keywords: central obesity, undiagnosed diabetes melitus, Pekanbaru